Analysis of Mangrove Leaf Litter Decomposition Rate in Mangrove Ecosystem of Muara Pagatan, South Kalimantan - Selviani, Selviani; Zamani, Neviaty Putri; Natih, Nyoman Metta N; Tarigan, Nurhayati (Jurnal Kelautan Tropis, 2024)
Mangroves are the dominant ecosystem in coastal areas and estuaries and one of the most productive ecosystems in the world. Mangroves are an essential component in a complex food chain and have the potential for the life of various marine and terrestrial biotas, microorganisms, and macroorganisms. The decomposition of mangrove leaf litter by fungal bacteria produces nutrient source that is beneficial for fish, shrimps, and crabs. This study discusses the production and decomposition rate of mangrove leaf litter in the mangrove ecosystem of Muara Pagatan, South Kalimantan. With transect and litter trap methods, litter production during the observation ranged from 218.51 - 858.28 g/m2/45day. Of the four types of mangroves found, the highest litter production was found in Rhizophora mucronata mangrove species at 858.28 g/m2/45day, followed by Bruguiera gymnorrhiza species at 268.52 g/m2/45day, and the lowest litter production was Avicennia marina mangrove species at 222.9 g/m2/45day and Sonneratia alba at 218.51 g/m2/45day. The remaining dry weight during observation ranged from 1.06 g - 2.46 g. In sum, the highest litter productivition and decomposition rate was found in Rhizophora species and litter was not completely decomposed after 45 days.